2020
DOI: 10.2106/jbjs.19.00946
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Total Shoulder Arthroplasty with a Superior Augmented Glenoid Component for Favard Type-E1, E2, and E3 Glenoids

Abstract: Background: Uncorrected superior glenoid wear in patients managed with reverse total shoulder arthroplasty (rTSA) can result in increased complications, including baseplate failure. The present study quantifies the clinical and radiographic outcomes of patients with Favard type-E1, E2, and E3 glenoid deformity who were managed with rTSA with use of a superior or superior/posterior augmented glenoid baseplate. Methods: We retrospectively reviewed the records for 68 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A total of 13 retrospective cohort studies, case series, and prospective cohort studies comprising 919 patients were included with 919 shoulders analyzed (Table I). 4,5,7,32-40 The mean age of patients at their initial evaluation was 72.2 years (42 to 87). The mean follow-up was 40.7 months (24 to 120).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 retrospective cohort studies, case series, and prospective cohort studies comprising 919 patients were included with 919 shoulders analyzed (Table I). 4,5,7,32-40 The mean age of patients at their initial evaluation was 72.2 years (42 to 87). The mean follow-up was 40.7 months (24 to 120).…”
Section: Resultsmentioning
confidence: 99%
“…ten studies presented clinical examination findings to report preoperative and postoperative rOm measurements (Figures 2 to 5). 4,5,[32][33][34][35][38][39][40]45 metaanalysis of these included studies demonstrated a significant increase in forward flexion at follow-up (mean difference (MD) 58.5° (95% confidence interval (CI) 51.5° to 65.4°); p < 0.001; Figure 2). From subgroup analysis, an improvement was seen in both bone graft and augmented prosthesis groups.…”
Section: Resultsmentioning
confidence: 99%
“…Augmented glenoid baseplates were designed to conserve glenoid bone, increase prosthesis surface contact area with cortical bone, and better restore the native joint line when performing rTSA in eroded scapular morphologies [41,44,45]. Positive clinical results have been reported with augmented baseplates in a variety of types of eroded glenoids [83,[88][89][90][91]. Alternatively, bone grafting the glenoid can be used to lateralize the joint line.…”
Section: Rtsa Patient-specific Considerations On Biomechanicsmentioning
confidence: 99%
“…Jones et al compared autologous glenoid bone grafting with the use of metal-augmented baseplates, suggesting that both designs showed favorable results in addressing large defects and improved clinical outcomes. However, metal-augmented baseplates may result in lower rates of scapular notching with similarly lower complications such as graft resorption and glenoid baseplate loosening [ 59 , 60 , 61 , 62 ]. Recently, Nabergoj et al reported of satisfying clinical and radiological outcomes in patients with RTSA and concomitant bony and metallic augmentation for severe glenoid bone loss compared to patients with bony glenoid augmentation only [ 63 ].…”
Section: Implant Designmentioning
confidence: 99%